THE USE OF INTERNATIONAL LAW AS A MEANS FOR ACHIEVING WORLD PEACE - فخر الدين جلال (Dirasat in Economics and Business, 1976)
The great problem existing in our world today can be defined in terms of political anarchy, and although no nation desires war, at the present we still lack the know-how to avoid it. "What makes war possible is the fact that the relations of nations to one ancther are governed not by law, binding on all, but by the self-interest and the force of each nation."(l) After half a million years of effort the genius of man has been able to come out with the ultimate weapon, and the only limiting factor in the destructive power of this weapon depends on what a nation is willing to invest of her resources " in nuclear warheads and delivery systems, and today at least two states have a sufficient amount of these weapons on hand to wipe out mankind."(2) President Johnson was quite correct in his statement that "Peace is by far the most important problem we face; it is the assignment of the century." (3) Senator Fulbright„ contemplating this problem, commented, "Most of what we learn, certainly in the